Compromise in hard times? The impact of deglobalization on corporate social responsibility in the US–China supply chain - Cao, Yanming; Chen, Jengfang; Chen, Xiaomeng Charlene; Lu, Meiting (Journal of business finance & accounting, 2025)
This study examines the effect of the US–China trade tensions on the corporate social responsibility (CSR) performance of the Chinese suppliers most affected by the 2018 US tariff surges. Using a difference‐in‐differences approach, we find that Chinese suppliers with direct US corporate customers experience a significant decline in CSR performance, compared with their peers without direct US corporate customers. We also show that the adverse effect of tariff surges on Chinese suppliers’ CSR performance is concentrated among those with a strong cost leadership strategy. However, the CSR performance of Chinese suppliers that have direct US corporate customers with high CSR awareness is not affected by the tariff surges. Further analyses reveal that the negative effects of the trade tensions on CSR performance are felt most strongly by the employees of Chinese suppliers. Taken together, despite the challenges posed by the deglobalization wave to the diffusion of CSR across global supply chains, the increasing demand for CSR involvement from US corporate customers can exert significant pressure on Chinese suppliers’ CSR performance.